2011
DOI: 10.1007/s00262-011-1007-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced programmed death 1 (PD-1) and PD-1 ligand (PD-L1) expression in patients with actinic cheilitis and oral squamous cell carcinoma

Abstract: PD-1 and PD-L1 can be involved in tumor escape, and little is known about the role of these molecules in oral tumors or pre-malignant lesions. In the present study, we investigated the expression of PD-1 and PD-L1 in the blood and lesion samples of patients with actinic cheilitis (AC) and oral squamous cell carcinoma (OSCC). Our results showed that lymphocytes from peripheral blood and tissue samples exhibited high expression of PD-1 in both groups analyzed. Patients with AC presented higher percentage as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…In the present study, we first observed that Tim-3 and PD-1 expression was up-regulated on circulating CD8 + T cells in CRC patients, a finding consistent with previously study that the expression of PD-1 is significantly higher in patients with cancer relative to the levels in healthy controls, such as T-follicular helper cells lymphoma [ 25 ], head and neck cancer [ 26 ], oral squamous cell carcinoma [ 27 ], and ovarian cancer [ 28 ]. Next analysis showed that Tim-3 + PD-1 + CD8 + T cells in CRC patients are significantly higher than that in healthy donors.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we first observed that Tim-3 and PD-1 expression was up-regulated on circulating CD8 + T cells in CRC patients, a finding consistent with previously study that the expression of PD-1 is significantly higher in patients with cancer relative to the levels in healthy controls, such as T-follicular helper cells lymphoma [ 25 ], head and neck cancer [ 26 ], oral squamous cell carcinoma [ 27 ], and ovarian cancer [ 28 ]. Next analysis showed that Tim-3 + PD-1 + CD8 + T cells in CRC patients are significantly higher than that in healthy donors.…”
Section: Discussionsupporting
confidence: 92%
“…However, studies with animal models and cancer patients have also shown that combining antibody blockade of the PD‐1/PD‐L1 axis with other forms of immunotherapy can lead to more meaningful clinical responses 32, 33, 34, 35. Approaches to block checkpoint signals have not been previously tested for their capacity to prevent premalignant lesion progression to cancer, despite indications of subjects with premalignant lesions having increased expression of PD‐L1 and PD‐1 + cells36, 37. The current study tested the immunological and clinical effects of PD‐1 blocking antibody treatment in a mouse 4NQO carcinogen‐induced premalignant oral lesion model that progresses to oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One such study showed increased expression of PD‐L1 within premalignant respiratory papillomas and suggested that this was indicative of immune exhaustion 36. Results of a study of patients with actinic cheilitis, an oral premalignant lesion that can progress to oral cancer, showed increased levels of PD‐1 + cells within the peripheral blood compared to that seen for controls, although levels were greater within the cancer tissue compared to levels in the premalignant lesions 37. Also shown in this study was PD‐L1 expression within premalignant lesions, although PD‐L1 expression was greater within HNSCC tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of PD-1 correlates with the prognosis of HCC (hepatic cell carcinoma) patients and raises the rate of recurrence 54, 55. A recent research demonstrated enhanced PD-1 expression in actinic cheilitis and oral squamous cell carcinoma 56. It is highly likely that the impairment of tumor-infiltrating T lymphocyte functions is due to the expression of PD-1 on the effector cells 57.…”
Section: Structure and Function Of Pd-1mentioning
confidence: 99%